Factors that support teachers as educational professionals doing doctoral studies: an integrative literature review - Van Doorsselaere, Joris (Frontiers in Education, 2024)
In recent decades, various initiatives have been established to support the professional development of teachers and their school context. In some cases, they provide teachers the opportunity to combine their profession with doctoral studies. This paper explores factors that support teacher research as part of school practice and academia. It takes the perspective of teachers as a starting point and examines their experiences through the lens of the learning potential of boundaries. A review of empirical studies was conducted from various international educational contexts through an integrative literature review. The selected empirical studies (n = 13) contributed to a better understanding of the complexity of this undertaking, and three themes were generated as main factors: (1) a stimulating school culture; (2) engaging with the academic community; (3) and aligning the research design with the practitioners’ needs.